2003
DOI: 10.1212/01.wnl.0000048207.28790.25
|View full text |Cite
|
Sign up to set email alerts
|

Infantile ascending hereditary spastic paralysis (IAHSP)

Abstract: The syndrome of IAHSP is genetically heterogeneous, and no clinical sign can help to distinguish patients with and without Alsin mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 37 publications
2
50
0
1
Order By: Relevance
“…5,15,17 This sign was seen in 5 of our patients (55%) (Fig 2A, -B). In family III, it was present in the older patient but absent in the younger one.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…5,15,17 This sign was seen in 5 of our patients (55%) (Fig 2A, -B). In family III, it was present in the older patient but absent in the younger one.…”
Section: Discussionmentioning
confidence: 65%
“…Whereas findings of brain and spinal MR imaging may appear normal in some patients as in our patient 9, there is a spectrum of MR imaging findings seen in patients with HSP, including mild brain and spinal atrophy, high T2 signal intensity in the posterior limb of the internal capsule, unspecific white matter lesions, thinning of the corpus callosum, 3-10 and brain and cerebellar atrophy predominantly in the motor areas and pericentral gyri. 5 A quantitative 3D MR imaging study of the brain volume demonstrated marked brain atrophy associated with HSP compared with agematched controls, and it was more severe and involved both gray and white matter 16 in the complicated forms of HSP. In our study, 4 patients had mild cerebral atrophy and just 1 had mild cerebellar atrophy (patient 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AlsinLF contains three guanine nucleotide exchange factor (GEF) homologous domains consisting of a regulator of chromosome condensation 1 (RCC1), Rho guanine nucleotide exchanging factor (RhoGEF), and vacuolar protein sorting 9 (VPS9) (5). All known ALS2 mutations are nucleotide deletions causing a C-terminal truncation of alsinLF (5)(6)(7)(8)(9)(10). Patients with a C-terminally truncated alsinLF show a variety of infantile-onset motoneuronal disorders, including ALS, which involves both upper and lower motor neurons, and hereditary spastic paraplegia, which involves only upper motor neurons.…”
mentioning
confidence: 99%